ANALISIS PERUBAHAN KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT DALAM PARIS AGREEMENT PADA MASA PEMERINTAHAN JOE BIDEN - Fuad Rizki Satriyo; Ika Riswanti Putranti; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
The change in leadership from Donald Trump to Joe Biden brought a new policy direction for the United States. One of them is the Paris Agreement. Biden's concern for the issue of climate change led the United States to change its foreign policy in the Paris Agreement, namely ratification after it was previously issued during the Trump administration. This study presents the formulation of the problem